Chlorophyll-based photocatalysts and their evaluations for methyl orange photoreduction - Joshi, Meenal M.; Kamble, Sanjay R.; Labhsetwar, Nitin K.; Parwate, D. V.; Rayalu, Sadhana S. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Immobilization of chlorophyll on different functionalized mesoporous materials has been attempted. The replacement of butanediol with monoethanol amine has resulted in increase in chlorophyll loading by a factor of two. The maximum immobilization of chlorophyll was on MCM-41 functionalized with monoethanolamine MCM-41/MEA/Chl) as compared to other mesoporous materials. This material has been characterized using XRD, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy (SEM-EDX) and fluorescence spectroscopy. The photocatalytic reduction of methyl orange (MO)was studied using MCM-41/MEA/Chl as photocatalyst under the visible light. The photocatalytic reduction of MO was 0.396 mg/g of MCM-41/MEA/Chl photocatalyst as compared to 0.508 mg/g of TiO(2) for that of Degussa P-25 photocatalyst. The effect of various operating parameters like catalyst loading, initial concentration and intensity of light has also been studied. Photocatalytic property of chlorophyll-based photocatalytic material indicates that chlorophyll acts as a reaction center, which absorbs visible light and generates electron, which is transferred to different electron acceptors reducing MO into derivative of hydrazine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll-based photocatalyst; Mesoporous material; Methyl orange; Photoreduction

Visible light induced photoreduction of methyl orange by N-doped mesoporous titania - Joshi, Meenal M.; Labhsetwar, Nitin K.; Mangrulkar, Priti A.; Tijare, Saumitra N.; Kamble, Sanjay P.; Rayalu, Sadhana S. (Applied Catalysis A-General, 2009)
N-doped mesoporous titania was synthesized using templating method. Biopolymer chitosan was used as a template and also as a nitrogen source along with ammonium hydroxide. Three different types of N-doped mesoporous titania were synthesized by varying composition of chitosan and titania precursor. These photocatalysts were characterized using XRD, BET-SA, FTIR, UV-DRS, SEM-EDX and XPS analysis. The photocatalytic activity of mesoporous titania was studied by methyl orange (MO) photoreduction reaction. From the experimental results it was observed that the N-doped mesoporous titania (1:2) gives the highest photocatalytic reduction of MO as compared to N-doped mesoporous titania prepared with (1:1) and (1:3) stoichiometry. This could be due to the optimal level of `N' incorporation in the N-doped mesoporous titania (1:2). Photocatalysts reduce the MO dye into derivative of hydrazine. Photoactivity of N-doped mesoporous titania (1:2) is 1.0721 mg of MO reduced per g of TiO2 vis-a-vis 0.508 mg of MO reduced per g of TiO2 for Degussa P25 photocatalyst. The effect of various operating parameters like photocatalyst loading. initial concentration and intensity of light also has been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chitosan; MO photoreduction; N-doped mesoporous titania; Visible active photocatalyst

Photocatalytic degradation of phenolics by N-doped mesoporous titania under solar radiation - Mangrulkar, Priti A.; Kamble, Sanjay P.; Joshi, Meenal M.; Meshram, Jyotsna S.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Photoenergy, 2012)
In this study, nitrogen-doped mesoporous titania was synthesized by templating method using chitosan. This biopolymer chitosan plays the dual role of acting as a template (which imparts mesoporosity) and precursor for nitrogen. BET-SA, XRD, UV-DRS, SEM, and FTIR were used to characterize the photocatalyst. The doping of nitrogen into TiO2 lattice and its state was substantiated and measured by XPS. The photocatalytic activity of the prepared N-doped mesoporous titania for phenol and o-chlorophenol degradation was investigated under solar and artificial radiation. The rate of photocatalytic degradation was observed to be higher for o-chlorophenol than that of phenol. The photodegradation of o-chlorophenol was 98.62% and 72.2%, while in case of phenol, degradation to the tune of 69.25% and 30.58% was achieved in solar and artificial radiation. The effect of various operating parameters, namely, catalyst loading, pH, initial concentration and the effect of coexisting ions on the rate of photocatalytic degradation were studied in detail.